# Week 02 : Method of C haracteristics From now on we will study one by one classical techniques of obtaining solution formulas for

PDEs. The ﬁrst one is the method of characteristics, which is particularly useful when solving ﬁrst order equations. 1 . C lassiﬁcation of ﬁrst-order equations. The general form of ﬁrst-order PDE ( in R2 ) : F( x , y , u , u x , u y ) = 0, or in R3 : ( x , y) ∈ D ⊂ R2 . (1) ( 2) ( 3) ( 4)

F( x , y , z , u , u x , u y , u z ) = 0. Often the following notation is used in 2D: p = ux , q = u y thus the equation can be written as F( x , y , u , p, q) = 0. The linear equations can be classiﬁced into the following cases, from easier to more diﬃcult: 1 . Linear: 2. Semi-linear: 3. Quasi-linear: 4. General case. F( x , y , u , u x , u y ) = a( x , y) u x + b( x , y) u y + c( x , y) u − d( x , y) . F( x , y , u , u x , u y ) = a( x , y) u x + b( x , y) u y − c( x , y , u) . F( x , y , u , u x , u y ) = a( x , y , u) u x + b( x , y , u) u y − c( x , y , u) .

( 5) ( 6) ( 7)

2. Method of characteristics. We try to ﬁnd a method to solve the general ﬁrst-order quasi-linear equation a( x , y , u) u x + b( x , y , u) u y = c( x , y , u) . ( 8)

Let’ s start by thinking geometrically. Consider the 3 dimensional space with coordinates ( x , y , u) . Assume that u = u( x , y) is a solution to the equation, it is clear that it represents a surface in the ( x , y, u) space. Now we explore the geometrical meaning of the equation. Observe that the equation can be written in the form of an inner product         a( x , y , u) a( x , y , u) ux ux  b( x , y , u)  ⊥ u y  .  b( x , y , u)  ·  u y  = 0 ( 9) c( x , y , u) −1 c( x , y , u) −1 Therefore all we need to do is to understand the relation between the vector
¡

First introduce a new function Ψ : R

3

R through

Φ ( x , y , u) = u − u( x , y) .

Note that in the RHS of the above, the ﬁrst u is a variable, the second u is a function. For example, suppose u( x , y) = x 2 + y 2 , then the corresponding Φ ( x , y, u) = u − x 2 + y 2 . Now we easily see that     Φx ux  uy  = −  Φ y  = − Φ. (11) Φu −1

 

 ux uy  − 1

and the solution. ( 1 0)

y . quasi. 3( b) ) Find the general solution of the equation a u x + b u y = 0. y . y) . ( 1 9) . Example 5. Conversely. U) ( 1 4) ds must be contained in one of the solution surfaces. y . y . As we will see soon.linear PDE a( x . y) . y. The characteristic equations are dx d y du = = . ( § 2. y . b are constant. 1 . b 0 a ( 20) a . Remark 3. We have shown that the equation is equivalent to the geometrical requirement   that is any  X( s)  Y( s)  U( s) is tangent to the solution surface u = u( x . we will show how to apply this method. u)  is perpendicular to the vector    ux uy  − 1 which that the vector curve a of  b  . any surface “woven” by such integral curves is a solution surface. We start from the simplest case. Y . any integral satisfying dX = a( X . ψ are obtained through solving the characteristic equations. The above understanding leads to the following “method of characteristics” due to Lagrange. 3. y) . We start with the simplest case. and any intersection of the level sets of φ and ψ is a solution of the characteristic equations dx d y du = = . a b c ( 1 7) ( 1 5) Remark 2. U) ( 1 3) ds dU = c( X . a ( x . The curves mentioned above are called the families of characteristic curves of the equation. u) and ψ( x . U) ( 1 2) ds dY = b( X . b±d b d ( 1 8) In the following. 8. the main technique in getting φ and ψ is   a c = b d a±c a c = = . As a consequence  a  b  c On the other hand. a  b  c  Φ ( and also − Φ ) is a normal vector of the surface Φ = 0. As we will see. c   Now we summarize. Equations with constant coeﬃcients. from the equation we know that must be tangent to the surface u = u( x . As a consequence. Remark 4. The general solution of a ﬁrst. is perpendicular to the solution surface u = u( x . Solving linear ﬁrst-order equations.order. u) . Y . u) satisﬁes F( φ . y . u)  b ( x . b . u)  c( x . ψ) = 0. y . Y . Theorem 1 . And each F gives a solution to the original equation.Recall   ux  uy  − 1 means that geometrically. u) u y = c( x . u) u x + b( x . 3. c and d are just constants. φ . ( 1 6) where F is an arb itrary function of φ( x . Solution. where a .

We write the characteristic equations dx dy du = = . 5( a) ) Oftentimes. ( C auchy problem. It is their values that are arbitrary constants. u) = 0 u = f( a y − b x) . For ψ. ( 25) Solution. Some times people use the following “method of characteristics”:         ( 31 ) ( 32) ( 33) ( 34) . u( x . a b d− cu We have dx dy = d( b x − a y) = 0. Remark 8. the solution satisﬁes for any function F. This means for an arbitrary function f. For example. 8. From the above example we know that the general solution takes the form u = f( 2 x − 3 y) . we obtain Therefore   ( 26) f( 2 x) = sin x x f( x) = sin . d 0) What happens when the c. the value of the solution along some speciﬁc curve in the plane is prescribed. One should keep in mind that neither φ or ψ can involve arbitrary constants. In the above. one may be tempted to conclude d u − C e− a −1 − 1 cx =0 and try to use u − C e − a c x as ψ. y) = sin   As a consequence and gives Example 7. F( a y − b x . notice that thus we can take d( a y − b x) = a d y − b dx = 0. Example 9. ( c. solve 3 u x + 2 u y = 0. u) and ψ( x . y . y . dψ = 0 along the characteristics. § 2. 2 ( 27) u( x . ψ = a y − b x. ψ = ea − 1 down ( 28) ( 29) ( 30) cx u − c− 1 d F( φ . ψ) = 0 u = c− 1 d + e − a − 1 cx f( b x − a y) . Now substituting this into the initial condition. d are not 0? The method still works. 0) = sin x. Example 6. This is obviously wrong as d somehow disappeared. ( 21 ) ( 22) ( 23) ( 24) As a consequence. u) such that d φ = 0. a b −1 −1 dx du du = = a− 1 d − a− 1 c u u = C e − a c x + c− 1 d d e a c x u − c− 1 d = 0 a d− cu dx φ = b x − a y. Obviously we can take φ = u. 2 2x−3y .What we need are two functions φ( x .

x y 2xy dx d y = y x ( 48) ( 49) . −x y 1 dy dx = y −x   ( 38) ( 39) y dx + x dy = 0 d( x y) = 0. 8. Pick any two of them. If you can ﬁnd general solutions. One may wonder. Example 1 2. ( 47) Solution. Finally represent s . ψ = u − log y.First solve then solve dx = a. 3. Equations with non-constant coeﬃcients. ds dy =b ds ( 35) ( 36) us + c u = d to obtain the solution u in the form u = u( s . F( x y . ( 37) dx d y du = = . This is equivalent to our method but considerably more complicated to use. Remark 1 0. But this fails when any coeﬃcient involves all other variables. ( 40) ( 41 ) ( 42) ( 43) ( 44) ( 45) ( 46) d y du = 1 y d( u − log y) = 0. ( § 2. u − log y) = 0 u = log y + f( x y) . 2. then using the value on y = x 2 to determine the arbitrary function involved. − Find the general solution The characteristic equations are Using dx d y du = = . Anyone who does not believe this should try using this method to the following examples with non-constant coeﬃcients. One way to systematically ﬁnd φ and ψ is the following. The characteristic equations are Using we obtain Thus φ = x y. with u = 2 on y = x 2 . t) . from we obtain du = d log y As a consequence we can take Putting these together we obtain which gives   y u y − x ux = 1 . We need to ﬁrst ﬁnd the general solution. ( § 2. On the other hand. 8. then you have φ and ψ. how to ﬁnd out φ and ψ eﬃciently? Unfortunately there may not be any short-cut. Example 1 1 . 3( h) ) Find the general solution of Solution. y and obtain the solution. 5( c) ) Find the solution of the following Cauchy problem: x ux + y u y = 2 x y . The characteristic equations consists of three equations. t by x .

Example 1 3.   Determine the solution. Solving semi-linear ﬁrst-order equations. ( 61 ) ( 62) ( 63) ( 64) . ( § 2. ( 65)   du u =− +2 dy y   du = 2 x dy = 2 y dx = x dy + y dx = d( x y)   y =0 x can take φ = y . that is y . Example 1 4. 5( g) ) Solve x ux + y u y = u + 1 Solution. 8. y) = x y + 2 − 4. . x 2 = 2. ( § 2. The characteritic equations are dx dy du = = x y u+1 ( 66) with u( x . 8. y) = x 2 on y = x 2 . 3( g) ) Find the general solution of the following equation: y 2 u x − x y u y = x ( u − 2 y) . y x 3 u( x . we have As a consequence   x 3 + f( x) = 2 f( x) = 2 − x 3 .we obtain d On the other hand. x ( 53) ( 54) ( 55) ( 56) ( 57) ( 58) ( 59) ( 60) d( ( u − y) y) = 0. dy du dx = = . y ( u − y) = 0 u = y + y− 1 f x2 + y2 . We have u = 2 along y = x 2 . The characteristic equations are From we have On the other hand. − x y x ( u − 2 y) y2 dy dx = y2 − xy   Solution. x d( u − x y) = 0 ( 50) ( 51 ) ( 52) y . u− xy =0 x u=xy+ f u x . d( u − y) u− y =− y dy   Thus we take Now gives ψ = y ( u − y) . Using the formula for the general solution. F x 2 + y 2 . we have therefore The general solution satisﬁes F − ψ = u − x y. we have d x2 + y2 = 0 dy du = − x y x ( u − 2 y)   φ = x2 + y2 .

( § 2. ( 78) with u = 1 on y = 0. dy du dx = = . − u u 2 + ( x + y) 2 u     ( 80) ( 81 ) ( 82) dx dy = u −u d( x + y) = 0 φ = x + y. 8. the solution is given by F x 2 − ( y + u) 2 . φ = x 2 + ( y + u) 2 . y y +x x x −1 − 1 = y+ 5. in the above we can also use d y d( x + u) = x+u y Thus the formula may not be unique. 3( f) ) Find the general solution of ( y + u) u x + y u y = x − y. . ( § 2. x ψ= u+1 . x 2 = x 2 f( x) = x + x − 1 . dy du = − u u2 + φ2 ψ = e2 y u2 + φ2 . ( 79) Solution. Remark 1 6. Solving quasi-linear ﬁrst-order equations. we have d( y + u) dx = y+u x d x 2 − ( y + u) 2 = 0. y) = x y . Example 1 5. ( 76) As a consequence. x ( 67) ( 68) ( 69) ( 70) x2 − 1. y ( 71 ) u=xf y − 1. d( x − y) du = x− y u       d u 2 − ( x − y) 2 = 0. Example 1 7. x x f( x) − 1 = u x . The characteristic equations are ( 73) ( 74) ( 75) From this we have Thus we can take On the other hand. Note that.which easily lead to φ= Thus Now the Cauchy data implies thus As a consequence u( x . 8. The characteristic equation are We have Then we have dy du dx = = . y x− y y+u   ( 72) Solution. u 2 − ( x − y) 2 = 0. 5( h) ) solve u u x − u u y = u 2 + ( x + y) 2 ( 77) d x+u y = const.

z 2 + y2 x2 + y2 which gives u = f x 2 + y2 . Clearly one can take φ = u. 8. 0 y z − x z x y ( x2 + y2 ) This time we need three invariants. K eep in mind that this f will be determined once some C auchy data is given. ψ) = ψ − φ 2 + 1 e 2 y u 2 + ( x + y) 2 − 1 + ( x + y) 2 = 0 u= ± 1 + ( x + y) 2 ( 83) ( 84) ( 85) .     dy dz = − xz xyφ dy dz = − z yφ d z 2 + y2 φ = 0 η = z 2 + y 2 φ. z 2 + y2 x2 + y2 for arbitrary f. we observe       ( 87) Solution. 1 + φ 2 ≡ 0. ( 90) Therefore the solutions are obtained by setting F u . F( φ .Now from the Cauchy data we have Therefore eﬀectively F has to be and the solution satisﬁes which leads to F φ . 1 ( 93) =0 ( 92) 1 . dy dz du dx = = = . ψ and η. For the second invariant. ( § 2. 8( d) ) Solve the following equation y z u x − x z u y + x y x 2 + y 2 u z = 0. The characteristic equations are ( 88) ( 89) The last invariant can be obtained through   dx dy = yz − xz dx dy = y −x d x2 + y2 = 0 ψ = x2 + y2 . The method of characteristics can be applied to higher dimensional problems with no diﬃculty in principle – it indeed becomes more diﬃcult in practice! Example 1 8. ( 86) e − 2 y − ( x + y) 2 1 /2 6. x2 + y2 . Equations with more than two variables. let’ s denote them by φ . ( 91 ) .